THE APPLICATION OF CELL-FREE FETAL DNA (cff-DNA) AND SIBLINGS DNA METHODS IN THE PROCESS OF PATERNITY TEST THROUGH CODIS STR LOCI (CSF1PO, THO1, TPOX, AND vWA) - Yudianto, Ahmad; Kurniawan, Arofi; Koesbardiati, Toetik; Faisol, Achmad; Setiawan, Fery; Furqoni, Abdul Hadi; Andriani Fauziah, Yessi (African Journal of Infectious Diseases (AJID), 2021)
Background: The non-invasive cff-DNA and siblings DNA methods are the latest breakthroughs in the forensic identification process. The use of cff-DNA and siblings DNA as non-invasive techniques in the forensic identification process has, hitherto, not been widely proven. Methods and Materials: This was an analytic observational study. The sample of this study consisted of peripheral blood of women in the second trimester of pregnancy and their two biological children. The kinship analysis was carried out through siblings' DNA and cff-DNA from the mothers through CODIS STR loci (CSF1PO, THO1, TPOX, and vWA). Results: The means of allele sharing between full siblings in loci CSF1PO, THO1, TPOX, and vWA were 0 (13.75%), 1 (44.75%), and 2 (41.50%). The allele sharing found in the study is in line with the one in previous research conducted by Wenk (1998) and the theory proposed by O'Connor (2011), indicating that one allele sharing dominates, contrasting with the finding of previous research conducted by Sosiawan (2020) revealing that 2-allele sharing was more superior. The variation is caused by the ethnicity having a different genetic contribution among the population. The variation can be attributed to historical and demographical processes leading to genetic drift. Conclusion: The mean of SI in 1 allele sharing in CODIS STR loci (CSF1PO, THO1, TPOX, and vWA) has the highest value of 44.5%. The use of cff-DNA of pregnant women as one of the non-invasive techniques can serve as an alternative material in a paternity test.